Will AI Completely Automate Medical Diagnosis by 2040? A Look at the Future of the 'Human-in-the-Loop' - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming the landscape of medical practice, with diagnostic imaging and patholog...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care